Cabaret finite‐difference schemes for the one‐dimensional Euler equations - Goloviznin, V. M.; Hynes, T. P.; Karabasov, S. A. (Mathematical Modelling and Analysis, 2001)
In the present paper we consider second order compact upwind schemes with a space split time derivative (CABARET) applied to one‐dimensional compressible gas flows. As opposed to the conventional approach associated with incorporating adjacent space cells we use information from adjacent time layer to improve the solution accuracy. Taking the first order Roe scheme as the basis we develop a few higher (i.e. second within regions of smooth solutions) order accurate difference schemes. One of them (CABARET3) is formulated in a two‐time‐layer form, which makes it most simple and robust. Supersonic and subsonic shock‐tube tests are used to compare the new schemes with several well‐known second‐order TVD schemes. In particular, it is shown that CABARET3 is notably more accurate than the standard second‐order Roe scheme with MUSCL flux splitting.Vienmačių Eulerio lygčių sprendimas CABARET3 baigtinių-skirtumų schemomisSantrauka. Šiame straipsnyje nagrinėjamos kompaktiškos antrosios tikslumu eilės baigtinių skirtumų schemos, kuriose panaudota speciali išvestinių aproksimacija. Sprendžiamas vienmatis spūdžių dujų judėjimo uždavinys. Darbe pasiūlytas didesnio tikslumo schemų konstravimo metodas, kuriame išnaudojama informacija apie sprendinį iš žemesnio laiko sluoksnio. CABARET3 schema yra dvisluoksnė, todėl jos realizavimo algoritmas yra ekonomiškas. Pateikiami skaičiavimo eksperimento rezultatai, kurie patvirtina, kad CABARET3 schema yra tikslesnė už antrosios tikslumo eilės Roe schemą, naudojančią MUSCL srauto išskaidymą.First Published Online: 14 Oct 2010